Age- and gender-specific reference intervals for serum glucose levels in school children measured by an Advia 1650 chemistry analyzer - Tamimi, Waleed; Tamim, Hani; Felimban, Naila; AlMutair, Angham; Altwaijri, Yasmin; AlAlwan, Ibrahim (Journal of Pediatric Biochemistry, 2012)
The prevalence of diabetes mellitus among adults has increased in developed and developing countries. However, less attention has been focused on children, including establishing age- and gender-specific reference intervals for serum glucose levels. In this study, we sought to establish these interval values among Saudi children. In 2006, male and female school children from diverse socioeconomic levels in Riyadh, Saudi Arabia were selected for a cross-sectional study of blood glucose using a cluster sample design. Tanner stages were ascertained during physical examination. Blood samples from 1216 healthy school children aged 6 to 16 years – 514 (42%) boys and 702 (58%) girls – were analyzed for glucose using an Advia 1650 chemistry analyzer and a hexokinase assay. Reference intervals based on Tanner stages and age were established by calculating the mean and the 2.5th and 97.5th percentiles. The average blood glucose level was higher in boys than in girls. There were no significant differences between boys and girls at each Tanner stage. Therefore, the combined reference intervals for glucose levels, which were calculated to be (3.2–6.6), (3.4–6.6), (3.6–5.9), (3.6–6.9), and (3.2–6.4) for Tanner stages I, II, III, IV, and V respectively, can be used for both genders. However, significant differences were observed between boys and girls for BMI, height, and weight at all Tanner stages except stage IV. Unlike children in other developing countries, Saudi children do not have lower serum glucose levels than their Western counterparts. We believe that these findings reflect changing dietary habits and increasing affluence in Saudi Arabia. The reference intervals established in our study may aid in the early assessment of cardiovascular risk in Saudi pediatric populations.
Keywords: Reference intervals; glucose; children